Educational Diplomacy And Latvia: Broadening The Scope Of Diplomatic Studies With A Focus On Asia - Šime, Zane (AEI Insights, 2023)
The existing body of literature on educational diplomacy and talent flows should be broadened with insights from understudied countries and geographic areas. Such a research direction is relevant to the balanced mobility considerations included in the Asia-Europe Meeting Education Process. This study concerns the increasing inflow of students in Latvia from Asia. It is motivated by the growing interest across the Asia-Europe Meeting partner countries to analyse international student pathways. Compared to the world’s leading higher education destinations, Latvia does not operate a wealth of resources for educational diplomacy. However, since educational diplomacy is a relatively novel term in the Latvian setting, the impact of Latvia’s granted scholarships and the overall pool of international students welcomed in Latvia remains an understudied area of the general international interconnectedness of the country with Asia and beyond. It is a promising area for further exploration of how ties fostered through higher education support the Latvian diplomatic aspirations spanning well beyond the rather narrow academic focus on the talent flows across the higher education destinations of the Baltic Sea Region, as well as policy and academic attention paid to the Latvian diaspora worldwide. The shifting student pathways and collaborative networks invite paying continuous attention to the evolving interconnections across Europe and Asia.